STEREOTYPES AND PREJUDICES IN A PLURALISTIC SOCIETY: PERSPECTIVES OF ISLAMIC EDUCATION IN BUILDING AN INCLUSIVE AND TOLERANT LEARNING ENVIRONMENT IN INDONESIA - Murdianto (ARMADA : Jurnal Penelitian Multidisiplin, 2023)
This research aims to analyze the phenomenon of stereotypes and prejudices in pluralistic societies and examine the role of Islamic education in building an inclusive and tolerant learning environment in Indonesia. The approach used is qualitative with a descriptive-analytical design through participatory observation, in-depth interviews, and documentation studies in Islamic educational institutions in Lombok. The research subjects include Islamic Religious Education teachers, school principals, and students from diverse backgrounds who were selected purposively. The results of the study show that stereotypes and prejudices still appear in students' social interactions, influenced by internal and external factors such as family environment, media, and limitations of cross-group interaction. Islamic education has a strategic role in reducing prejudice through the internalization of the values of tasamuh, 'adl, and ukhuwah insaniyah, which are implemented through dialogical learning, contextual curriculum, and inclusive school culture. In addition, the role of teachers as agents of social change and school leadership support are key factor in the successful implementation of inclusive education. This research emphasizes that Islamic education not only functions as a transmission of religious values but also as an instrument of social transformation in building harmony in a multicultural society.